Pemasangan Pembangkit Listrik Tenaga Surya (PLTS) untuk Mushalla Al Barkah di Kelurahan Limau Manis, Kecamatan Pauh, Kota Padang - Yandri, Valdi Rizki; Wiharti, Wiwik; Hendri, Zulka; Hendri, Lenny Novi (Jurnal Abdimas: Pengabdian dan Pengembangan Masyarakat, 2024)
The Al Barkah prayer room is located in Limau Manis Village, Pauh District, Padang City and still frequently experiences power outages. This condition often causes disturbances to residents when carrying out their worship, so an alternative source of electricity is needed, namely a Solar Power Plant (SPP). The electrical load in this prayer room consists of 8 lamp units. The optimal time for SPP energy convertion is morning until midday, around 08.00 to 12.00. The effect of temperature on the efficiency of the SPP system can be seen from the decrease in power produced even though the intensity of sunlight is still high. This analysis provides a general overview of the performance of SPP without load in one day, showing the importance of monitoring temperature and sunlight intensity to optimize electrical energy output. At noon, around 12:00 to 13:00, the SPP system reaches peak energy conversion. The voltage and current reached their highest values, with power reaching 146.2 W at 12:00 and decreasing slightly to 119.7 W at 13:00 even though the sun's intensity reached its highest peak, namely 1115 W/m². In the afternoon, from 14:00 to 17:00, it shows a significant drop in voltage, current and power. At 14:00, the power produced is still quite high, namely 142.1 W, with a solar intensity of 1009 W/m². However, after 15:00, the power generated decreases drastically, only reaching 36.3 W at 15:00 and decreasing further to 23.5 W at 17:00, with a solar intensity of only 100 W/m².